1991
DOI: 10.1016/s0022-5347(17)37705-4
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Low and High Volume Anesthetic Jelly as a Lubricant and Pain Reliever During Cystoscopy

Abstract: To evaluate the influence of the volume of 2% lidocaine jelly as an anesthetic during cystoscopy 241 men and women received either 11 or 20 ml. jelly intraurethrally in a randomized, double-blind fashion. Pain was recorded on a visual analogue scale by the patient and on a 3-level scale by the physician. The pain scores according to the visual analogue scale were significantly higher in the patients given 11 ml. jelly than in those given 20 ml. when all patients in the study were analyzed. There was no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The value of adequate volume during rigid cystoscopy was outlined by Goldfisher and associates 29 and confirmed by Brekkan and coworkers 30 and Holmes and colleagues. 36 They found that a minimal volume of 20 mL is necessary to increase anesthetic efficacy.…”
Section: Decreasing Pain During Cystoscopymentioning
confidence: 79%
See 2 more Smart Citations
“…The value of adequate volume during rigid cystoscopy was outlined by Goldfisher and associates 29 and confirmed by Brekkan and coworkers 30 and Holmes and colleagues. 36 They found that a minimal volume of 20 mL is necessary to increase anesthetic efficacy.…”
Section: Decreasing Pain During Cystoscopymentioning
confidence: 79%
“…30 They evaluated the influence of instilled volume (11 vs 20 mL) in pain perception and found a significant pain reduction in the group of male patients with the use of 20 mL of the anesthetic lubricant. No difference was found among the two groups of women [Ib, A].…”
Section: Cystoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,9 Slow instillation was chosen for this study as it has been reported that a slow rate of jelly instillation is associated with less pain. 6 In our study, patients in group A (5 minutes intraurethral dwell time) and B (10 minutes intraurethral dwell time) experienced significantly more pain as compared to patients in group C (15 minutes intraurethral Jelly was instilled 5, 10, 15, and 20 minutes before start of the procedure in Group A, B, C, and D patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] For men, 20 mL of 2% lidocaine jelly instilled slowly before start of the rigid cystoscopy procedure is considered optimum for maximum pain relief. 5,6 However, the optimal intraurethral dwell time of the anesthetic jelly for maximal pain relief, that is, ''how long a urologist should wait after anesthetic jelly instillation before starting the procedure'' is not known with only a few studies addressing this issue. 1,7 In this prospective, randomized study, we look at varying dwell times in an attempt to define the ''optimum dwell time'' for maximal pain relief.…”
Section: Introductionmentioning
confidence: 99%